2013
DOI: 10.1177/1012690213490520
|View full text |Cite
|
Sign up to set email alerts
|

Openly lesbian team sport athletes in an era of decreasing homohysteria

Abstract: Sociologists who examine the issue of lesbians in American sport in the 1980s and 1990s normally found overt and covert mechanisms of social discrimination.However, homophobia has been on a rapid decline over previous decades, and studies show attitudes toward female homosexuality in sport have improved since the research conducted on lesbian athletes in the mid-1990s. This article uses data collected between that epoch and current studies to analyze athletic narratives of openly lesbian team sport athletes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 28 publications
(28 reference statements)
7
81
1
Order By: Relevance
“…The secrecy surrounding hazing makes it difficult to measure and quantify. Ethnographic studies provide some qualitative accounts109 120 but, by its very nature, it is rare for victims of hazing to speak out, and thus unusual for medical staff and other entourage members to become involved in evaluation or support.…”
Section: Mechanisms For Harassment and Abusementioning
confidence: 99%
“…The secrecy surrounding hazing makes it difficult to measure and quantify. Ethnographic studies provide some qualitative accounts109 120 but, by its very nature, it is rare for victims of hazing to speak out, and thus unusual for medical staff and other entourage members to become involved in evaluation or support.…”
Section: Mechanisms For Harassment and Abusementioning
confidence: 99%
“…Additionally, the Australian cricket environment in the 1990s has also been described as hostile to lesbians (Burroughs, Ashburn, & SeeBohm, 1995). Likewise, in the American collegiate sport system, two of 12 athletes interviewed by Anderson and Bullingham (2015) in their recent research reported homophobic language being used by players on their team.…”
Section: Aim Of the Chaptermentioning
confidence: 99%
“…Within a conditionally tolerant climate, the issue is not lesbian participation but rather their visibility within sport; lesbians are allowed to participate providing they subscribe to a set of rules (Griffin, 1998). This environment has more recently been described as 'don't ask, don't tell' (Anderson, 2002;Anderson & Bullingham, 2015), a policy implemented until recently within the US military. Within a 'don't ask, don't tell' policy, athletes may temporarily emerge from the closet to reveal their sexual identity, but after the revelation, normal play is resumed, with teammates ignoring the incident.…”
Section: Aim Of the Chaptermentioning
confidence: 99%
See 2 more Smart Citations